1996
DOI: 10.1021/je960133t
|View full text |Cite
|
Sign up to set email alerts
|

Density, Refractive Index, Viscosity, and Speed of Sound in Binary Mixtures of 2-Ethoxyethanol with Dioxane, Acetonitrile, and Tetrahydrofuran at (298.15, 303.15, and 308.15) K

Abstract: Density, refractive index, viscosity, and speed of sound data in binary mixtures of 2-ethoxyethanol with dioxane, acetonitrile, and tetrahydrofuran are presented at (298.15, 303.15, and 308.15) K over the whole range of mole fractions at atmospheric pressure. These results are used to calculate excess molar volume, deviations in molar refractivity, viscosity, and isentropic compressibility. The calculated quantities are further fitted to the Redlich−Kister equation to estimate the binary interaction parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The effect of temperature on the index of refraction of the sample solution turns out to be a surprisingly significant issue to deal with from an experimental perspective. The temperature dependence of some common solvents – including acetonitrile – has been studied previously 28,29. Specifically, as the temperature decreases, the solvent's refractive index increases.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of temperature on the index of refraction of the sample solution turns out to be a surprisingly significant issue to deal with from an experimental perspective. The temperature dependence of some common solvents – including acetonitrile – has been studied previously 28,29. Specifically, as the temperature decreases, the solvent's refractive index increases.…”
Section: Resultsmentioning
confidence: 99%
“…Mixtures containing methylcyclohexane with different liquids have also been studied [14][15][16][17]. However, no such studies were reported on the mixtures of methylcyclohexane with aliphatic alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental densities, viscosities, and refractive indices of the pure materials are presented at temperatures of (288. 15, 298.15, and 308.15) K in table 1 along with the corresponding literature values [12][13][14][15][16][17][18][19][20][21].…”
Section: Methodsmentioning
confidence: 99%